A Case Study of Analyzing Emotional Exhaustion from A Medical Center in Taiwan - Lee, Yii-Ching; Huang, Chi-Hsuan; Rahman, Diniy Hidayatur; Yu, Chia-Hui; Wu, Hsin-Hung (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study uses a medical center in Taiwan as an example to analyze medical staff’s emotional exhaustion by independent sample t test and analysis of variance. Eight out of ten demographic variables are considered as essential variables to influence emotional exhaustion excluding respondents reporting events in the past 12 months and job status. The results show that female employees and employees who are not supervisors/managers tend to have higher burnout. Employees whose ages are 21–30, 31–40, and 41–50 years old also have a higher degree of fatigue. In addition, nurses are more stressful than the others in this medical center. The detailed post hoc analyses enable hospital management to identify employees with high burnout. Finally, this study also provides some recommendations to help hospital management reduce employees’ burnout.